Indicadores de qualidade para avaliação dos processos de gestão da informação - Monteiro, Samuel Alves (2015)
Analyzes the information management processes from theoretical models, from the point of view of the need to review the steps or stages of these processes. Define the central research problem: what are the quality indicators needed to evaluate the information management processes in organizations? It also contains peripheral issues that contributed to the definition of the core problem: why not evaluating information management or levels / stages of this process in organizations? how to know the effectiveness of execution of each phase of information management processes proposed by theoretical models of different authors? You can evaluate the information management processes through quality indicators? The overall objective of the research is to identify from certain scientific production, quality indicators that enable the assessment of the steps / stages of information management processes in organizations, established in theoretical models. The methodology is set in a theoretical research, which is characterized by allowing an immersion in the existing knowledge and available on the problem we propose to solve. The type of research was the literature. Information sources worked in this study were primarily scientific articles, coming from national and international journals in the field of Information Science; theses, dissertations and book chapters that deal with the theme of the study core, information management. The results pointed to the creation of a set of indicators arising from the literature. Finally, we consider that the study was significant and fundamental to the Information Science, in particular to the information management area and studies on assessment methodologies. We attach as an innovative factor for Information Science quality indicators proposition for the evaluation of information management processes, in particular, by the fact that these proposed indicators are potentially applicable and flexible its validation. It is also proposed the inclusion of a new stage / phase in the management of information, the evaluation stage.